2005
DOI: 10.1007/s00335-004-2454-5
|View full text |Cite
|
Sign up to set email alerts
|

A locus for eosinophilia in the MES rat is on Chromosome 19

Abstract: Matsumoto Eosinophilia Shinshu (MES) is a rat strain that spontaneously develops eosinophilia and eosinophil-related inflammatory lesions in many organs. We performed chromosomal mapping of the gene for eosinophilia by breeding backcross progeny. The onset of eosinophilia appeared to be delayed in the progeny compared with that in MES, with the prevalence of eosinophilia in the backcross progeny at 12 weeks of age being 22.5%. Genetic linkage analysis with marker loci indicated the major locus for eosinophilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In our previous study, we observed that the blood eosinophil count in (ACI × MES)F 1 × MES backcross rats homozygous for the mutant Cyba mes gene sacrificed at 12 weeks of age was significantly lower than in parental MES rats of the same age [14]. The reason for this difference was unclear.…”
Section: Hematologic and Histological Examinationmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous study, we observed that the blood eosinophil count in (ACI × MES)F 1 × MES backcross rats homozygous for the mutant Cyba mes gene sacrificed at 12 weeks of age was significantly lower than in parental MES rats of the same age [14]. The reason for this difference was unclear.…”
Section: Hematologic and Histological Examinationmentioning
confidence: 95%
“…Eosinophil-related gastroenteritis or aortitis are also observed. The primary cause of eosinophilia in MES rats is a loss-of-function mutation in the gene for cytochrome b(-245), alpha polypeptide (Cyba; also known as p22 phox ), which is an essential component of the superoxide-generating NADPH oxidase complex [14,19,20]. In a previous study, we bred and characterized a congenic rat strain in which the mutant Cyba mes gene was introduced into the background of a BN strain (BN.MESCyba mes ) [37].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we performed chromosomal mapping of the gene(s) associated with eosinophilia in MES rats by breeding (ACI × MES) × MES backcross progeny [2]. Blood eosinophil counts in the 328 backcrosses showed a broad distribution.…”
mentioning
confidence: 99%
“…Fifty-five rats with low eosinophil and neutrophil numbers and devoid of enlarged mediastinal lymph nodes were categorized as a normal group (Group 3). Genetic linkage analysis between abnormal phenotypes and microsatellite marker loci using the chi square test revealed that the major locus for eosinophilia (eosinophilia 1; eos1) was located in the telomeric region of the q arm of chromosome 19 [2]. Significant deviations in homozygosity of the MES allele were observed in the abnormal rats (Groups 1 and 2) at marker loci including D19Rat2 (Table 1).…”
mentioning
confidence: 99%
“…Eosinophil-related gastroenteritis and aortitis are also observed. The primary cause of eosinophilia in MES rats is a loss-of-function mutation in the gene for cytochrome b(-245), alpha polypeptide (Cyba; also known as p22 phox ), which is an essential component of the superoxide-generating NADPH oxidase complex [11,14,15]. As animal models for eosinophilia, three transgenic mouse strains overexpressing IL-5 with different genetic backgrounds have been developed [5,10,27].…”
Section: Introductionmentioning
confidence: 99%